Zooming in on climate change data - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
The agricultural sector will be hit hard by climate change. More than 265 million people are facing a five percent decrease in growing season duration in the next 40 years due to an increasingly variable and hotter climate sweeping across the globe. Climate change will affect all four aspects of food security, from availability and stability of food supplies to people’s access to and utilization of food. If we are to successfully tackle threats to food security, we need more robust climate data that will help us prepare and plan for these shifts. The CCAFS-Climate Data portal provides users with vigorous, high-resolution climate data that can help assess the impacts of climate change on agriculture.